Case Report: Severe rebound after withdrawal of fingolimod in a patient with neuromyelitis optica spectrum disorder - Lin, Wei; Chou, Chung-Hsing; Yang, Fu-Chi; Tsai, Chia-Kuang; Lin, Yu-Kai; Sung, Yueh-Feng (Frontiers in Immunology, 2023)
Purpose Fingolimod, an oral treatment for relapsing-remitting multiple sclerosis (RRMS), has been associated with a significant rebound in disease activity after therapy cessation. We described a patient with neuromyelitis optica spectrum disorder (NMOSD) who was previously diagnosed with RRMS and experienced fatal rebound syndrome after cessation of fingolimod. Case report A 54-year-old woman, previously diagnosed with RRMS, experienced relapse after orthopedic surgery. The diagnosis was later revised to NMOSD based on a positive aquaporin-4 antibody. Three weeks after converting the immunomodulator from fingolimod to azathioprine, severe disease reactivation was observed. Considering the multiple new and enlarging magnetic resonance imaging lesions, the temporal relationship between fingolimod cessation and symptom onset, and the relatively low possibility of disease reactivation within a short time, the diagnosis of fingolimod withdrawal syndrome was proposed. Although immediate steroid pulse therapy and plasma exchange were performed, the patient eventually died owing to a fulminant clinical course. Conclusion Fingolimod withdrawal syndrome is well known in patients with multiple sclerosis (MS). It can also occur in patients with NMOSD. Recognizing patients with NMOSD who present with MS-like manifestations, and avoiding drugs that may be harmful to patients with NMOSD, are important.